2005
DOI: 10.1016/j.jcis.2004.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica colloids on the rheology of viscoelastic gels formed by the surfactant cetyl trimethylammonium tosylate

Abstract: The effects of the addition of submicrometer-sized colloidal silica spheres on the linear and nonlinear rheology of semidilute solutions of a viscoelastic gel are studied. For a 1.4 wt% solution of the surfactant CTAT, a peak in the zero-shear rate viscosity eta(0) is observed at approximately equal weight percents of silica and CTAT. This peak shifts to lower silica concentrations on increasing either the CTAT concentration or the surface charge on silica and disappears when the CTAT concentration is increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 27 publications
5
43
2
Order By: Relevance
“…Herein, we found that the organic additive of OTAB was much more efficient in inducing the NaOA micellar growth than the inorganic Na 2 CO 3 . Compared with the previous studies on the mixtures of nanoparticles and wormlike micelles, most of them employed are cationic surfactants and opposite charged nanoparticles [19,20,22] that suffered serious disadvantages and limited their applications [15]. The present work showed detailed information about the interactions between anionic wormlike micelles and positivecharged nano SiO 2 , in which the presence of nano SiO 2 can also facilitate branched wormlike micelles formation in the NaOA/OTAB system as confirmed by rheology and cryo-TEM results.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Herein, we found that the organic additive of OTAB was much more efficient in inducing the NaOA micellar growth than the inorganic Na 2 CO 3 . Compared with the previous studies on the mixtures of nanoparticles and wormlike micelles, most of them employed are cationic surfactants and opposite charged nanoparticles [19,20,22] that suffered serious disadvantages and limited their applications [15]. The present work showed detailed information about the interactions between anionic wormlike micelles and positivecharged nano SiO 2 , in which the presence of nano SiO 2 can also facilitate branched wormlike micelles formation in the NaOA/OTAB system as confirmed by rheology and cryo-TEM results.…”
Section: Discussionsupporting
confidence: 65%
“…The present work showed detailed information about the interactions between anionic wormlike micelles and positivecharged nano SiO 2 , in which the presence of nano SiO 2 can also facilitate branched wormlike micelles formation in the NaOA/OTAB system as confirmed by rheology and cryo-TEM results. Compared with the previously reported cationic type systems [19,20,22], this anionic type nanoparticles and wormlike micelles mixtures may extend their applications in many fields, especially in that of crude oil recovery.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations